ANALISIS HUKUM GANTI RUGI TANAH MASYARAKAT UNTUK PEMBANGUNAN JALAN TOL MEDAN-KUALANAMU-TEBING TINGGI (STUDI DESA BANGUN SARI KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG) - Rizky Feb Riansyah Hasibuan; Muhammad Yamin; Hasim Purba; Rosnidar Sembiring (USU LAW JOURNAL, 2018)
ABSTRACT Bangun Sari Village Community, Tanjung Morawa Sub-district Deli Serdang Regency whose homes and land have been compensated by the Government for the construction of Medan-Kualanamu-Tebing Tinggi Highway, feels aggrieved by the government's policy to raise the recently replaced land price Loss or in 2016. In the period of 2013-2015 the people whose land and houses have been compensated at Rp.236.000/meter (two hundred thirty six thousand rupiah/meter) regardless of the status of land ownership of either the Certificate of Property (SHM) Or other rights basis are all paid at the same price. However, it is very different from some of the people of Bangun Sari Baru Village whose homes and land were compensated in 2016 have increased dramatically to 300% (three hundred percent) and added some additional clause items starting from non-physical losses (premium, Solatium, and transaction costs) and the compensation of the waiting period. Therefore, it is necessary to examine the basis of the compensation arrangement for land taken by the state for the public interest. Non-compliance with compensation for houses and land obtained by the community of Bangun Sari Village, Tanjung Morawa Sub-district of Deli Serdang Regency for the construction of Medan-Kualanamu-Tebing Tinggi Highway. Efforts that can be made by the people of Bangun Sari Village, Tanjung Morawa Sub-district, Deli Serdang Regency, due to inconsistency of compensation for houses and land that have been compensated by the Government for the construction of Medan-Kualanamu-Tebing Tinggi Highway.   Keywords: Toll Road, Public Interest and Indemnification